Dietary effect of Cissus populnea and Securidaca longepedunculata aqueous leave extracts on reproductive, haematological and biochemical parameters of African catfish Clarias gariepinus (Burchell, 1822) broodstocks - Aderolua, Ademola Zaid; Lawal, Muyideen Owonire; Okoronkwo, Luke Ikechukwu; Awobajo, Funmileyi Olubajo; Jesuniyi, Faith Iyanuoluwa (Aceh Journal of Animal Science, 2017)
The objectives of the present study were to evaluated gametes quality, haematological and biochemical parameters of the Clarias gariepinus brood stocks fed with varying concentrations of Cissus populnea (CP) and Securidaca longepedunculata (SL). Fish were fed with Diet 1 (control, 0 ml plant extract), Diet 2(0.5 ml/kg CP), Diet 3 (1.0 ml/kg CP), Diet 4 (0.5 ml/kg SL), Diet 5 (1.0 ml/kg SL) and Diet 6Â (0.5 ml/kg CP + 0.5 ml/kg SL) for 90 days. The results of haematocrit and red blood cell of treated groups were relatively similar to the control. The white blood cell and haemoglobin values were lower than the control group while the mean corpuscular volume, mean corpuscular haemoglobin were significantly difference across treatments however; an elevated glucose level was recorded in the treated groups. Also, the mean platelet volume and platelet distribution width were relatively similar across treatments. The serum testosterone, progesterone and estrogen were found to be higher in fish fed diet 2 (0.5ml/kg CP). C. populnea at 0.5 ml/kg significantly (p<0.05) improved eggs weight, fecundity, gonadosomatic index, % fertilization and hatchability. Male brood stocks fed diet 2 (0.5 ml/kg CP) recorded the highest values for sperm motility (56.67 Â± 0.33%), milt count and volume (820.33 Â± 0.33Ã106/ml and 1.80 Â± 0.05 ml respectively) across all groups. Similarly, fish fed diet 2 (0.5ml/kg CP) had the highest values for eggs weight (283.7Â±102.4g), fecundity (168,286 Â± 57157), gonadosomatic index (32.59 Â± 2.72), fertilization (62 Â± 20.4%) and hatchability (62.92 Â± 19.75%).The dietary supplementation of 0.5 ml/kg C. populnea extract highly enhanced the reproductive profiles of male and female C gariepinus brood stocks.